Evaluation of several vegetation indices to detect deep man-made bunkers using field spectroscopy - Melillos, George; Themistocleous, Kyriacos (My University, 2019)
This paper presents the results obtained from field spectroscopy campaigns for the detection of deep man-made bunker infrastructures in Cyprus. Several of vegetation indices combined with other in-band algorithms were utilized for the development of a vegetation index-based procedure aiming at the detection of deep man-made bunkers. The measurements were taken at the following test areas: Area (a) vegetation area covered with vegetation, in the presence of deep man-made bunker and Area (b) vegetation area covered with vegetation, in the absence of deep man-made bunker. The test areas were identified, analyzed and modeled under different scenarios. Comparing the two test areas, results have shown that there were differences in the spectral vegetation indices (SVIs).
Keywords: Remote sensing; Spectroscopy; Deep man-made bunker; Vegetation indices